Implications of the Book - Winniefridah Matsa (Springer, Cham, 2023)
The book shows interplay of marginality, migration and education. It has implications to policy makers on migration and education, migration and development, gender and migration, migration and children’s rights and marginality and education among others. The book suggests a look into issues of geo-physical, socio-economic, political and cultural marginalisation. It directs focus on a variety of forms of inequality and unequal access and provisions of resources resulting from state of marginality of Bulilima and Mangwe people of Zimbabwe with particular focus on migrants’ children. Although the book focuses mainly on marginalisation of migrants’ children, the Zimbabwe community as a whole experiences marginality. Non-migrant children live in marginal contexts also although their situation cannot be compared to that of migrants’ children.